2022
DOI: 10.3390/su14159381
|View full text |Cite
|
Sign up to set email alerts
|

Study on Low-Carbon Technology Innovation Strategies through Government–University–Enterprise Cooperation under Carbon Trading Policy

Abstract: This paper focuses on developing low-carbon technology (LCT) innovation in traditional enterprises under carbon trading policies. The Hamilton–Jacobi–Berman equation quantitatively investigates the coordination mechanism and optimal strategy of LCT innovation systems in conventional industries. A three-way dynamic differential game model is constructed to analyze three cases: the Nash disequilibrium game; the Stackelberg master–slave game; and the cooperative game with the optimal effort of universities, tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…They found that the regulatory policies could not always promote remanufacturing. Wang et al [24] studied the differential game of low-carbon technology innovation among governments, universities, and enterprises under the carbon-trading policy, established the equilibrium between technological innovation effort and environmental management effort, and found that the carbon trading price could significantly affect technological innovation efforts.…”
Section: Game On Carbon-emission Reduction Between Governments and En...mentioning
confidence: 99%
“…They found that the regulatory policies could not always promote remanufacturing. Wang et al [24] studied the differential game of low-carbon technology innovation among governments, universities, and enterprises under the carbon-trading policy, established the equilibrium between technological innovation effort and environmental management effort, and found that the carbon trading price could significantly affect technological innovation efforts.…”
Section: Game On Carbon-emission Reduction Between Governments and En...mentioning
confidence: 99%
“…The primary goal of the low-carbon policy is to reduce greenhouse gas emissions and achieve sustainable development [141]. The object of the low-carbon trading policy is to control carbon emission by constructing a carbon emission trading pricing mechanism [142].…”
Section: Impact Of Low-carbon Trading Policymentioning
confidence: 99%
“…In recent years, China's CO 2 emissions continued to increase, especially since 2000, carbon emissions continued to increase rapidly, and China became the world's largest country in terms of carbon emissions, and the issue of carbon emission reduction in China became the focus of the international community. In the face of increasingly serious environmental problems, China put forward the goal of "peaking carbon emissions by 2030 and achieving carbon neutrality by 2060" [3], and brought this goal into the overall layout of ecological civilization construction to achieve the goal of low-carbon transformation and contribute to global climate governance.…”
Section: Introductionmentioning
confidence: 99%